2020
DOI: 10.21037/atm-20-4630
|View full text |Cite
|
Sign up to set email alerts
|

Redo aortic valve replacement for prosthesis endocarditis in patients previously classified as high or prohibitive risk: a narrative review

Abstract: Transcatheter aortic valve implantation (TAVI) and sutureless aortic valve replacement (Su-AVR) enabled in the last years many patients at high or prohibitive risk to be treated for their severe symptomatic aortic valve stenosis. As often happens in medicine, new techniques bring not only new hopes, but also new problems. In recent years, alongside the lengthening of the life of these patients treated with TAVI or Su-AVR, cardiologists and cardiac surgeons have had to face the long-term complications associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The phenomenon of mutating epidemiology of infective endocarditis in high-income countries is related to substantial progress in the medical and surgical fields [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Therefore, an increase of 25–30% of contemporary cases of IE are acquired in the health sector, either due to the progressive increase in medical care offered during hospitalization or nosocomial admission, or to the possibility of contracting the infection on an outpatient basis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The phenomenon of mutating epidemiology of infective endocarditis in high-income countries is related to substantial progress in the medical and surgical fields [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Therefore, an increase of 25–30% of contemporary cases of IE are acquired in the health sector, either due to the progressive increase in medical care offered during hospitalization or nosocomial admission, or to the possibility of contracting the infection on an outpatient basis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Potential complications include paravalvular abscess formation, stroke, and bleeding, none of which were found in our cohort [ 23 ]. Differences in reported complication rates across studies may be attributed to variations in patients’ clinical characteristics, the surgical techniques employed, and postoperative care protocols [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, one patient of our cohort with surgical indication who survived the episode was later operated on in a second IE episode with no complications. Other authors have shown the importance of a multidisciplinary approach, within an Endocarditis team, in evaluating the surgical risk of IE patients and optimizing surgical decisions [ 28 , 29 , 30 ]. We speculate that patients with IE after TAVI should not be discarded for surgery based only on their comorbidity and complexity.…”
Section: Discussionmentioning
confidence: 99%